Current status and future advances of digital radiography and PACS. - Xinhua Cao (IEEE Engineering in medicine and biology magazine)
Describes the current status and future advances of two components in a large-scale digital healthcare delivery system: digital radiography (DR) and PACS, as well as their relationship with other healthcare information systems, hospital information systems (HIS), and electronic patient records (EPR). In DR, the authors review computed radiography and describe the current advances in DR technology. The measurements of spatial resolution, image contrast, and signal-to-noise ratio (SNR) of DR are given. In PACS, the authors emphasise DR and PACS integration and its utilization in several applications, including outpatient clinics, emergency rooms, imaging centers, and teleradiology. The importance of medical imaging informatics in the future practice of medicine based on integrated PACS is also outlined.